Strategic methods for the preparation of coumarin fused dihydroquinolines (CFDQ): A concise review - Reshmi Bose; Tamanna Pradhan; Bholanath Pakhira; Manas Roy; Subrata Dolui; Ambrish Singh; Tanay Pramanik (Results in Chemistry)
Coumarin-fused dihydroquinolines (CFDQs) are fascinating heterocycles that have become intriguing to medicinal chemists due to their outstanding bioactivity. Though there are different conventional methods used to synthesise CFDQs, they face challenges in terms of by-product formation, isolation difficulty, high costs, and environmental impact. In this review, we provide insight into green as well as conventional methods for the synthesis of CFDQs strategically and methodically. Furthermore, the formation of CFDQs depends on the inductive effect of diverse functional groups attached to the aromatic amines and aldehyde moiety. Predominantly, this review provides a concise overview of the synthesis of fused dihydroquinolines, highlighting the potential for future advancements in this field and addressing key considerations for aspiring scientists.